Performance of Glial Fibrillary Acidic Protein in Detecting Traumatic Intracranial Lesions on Computed Tomography in Children and Youth With Mild Head Trauma. (15th October 2015) - Papa, Linda; Zonfrillo, Mark R.; Ramirez, Jose; Silvestri, Salvatore; Giordano, Philip; Braga, Carolina F.; Tan, Ciara N.; Ameli, Neema J.; Lopez, Marco; Mittal, Manoj K.
Abstract: Objectives: This study examined the performance of serum glial fibrillary acidic protein (GFAP) in detecting traumatic intracranial lesions on computed tomography (CT) scan in children and youth with mild and moderate traumatic brain injury (TBI) and assessed its performance in trauma control patients without head trauma. Methods: This prospective cohort study enrolled children and youth presenting to three Level I trauma centers following blunt head trauma with Glasgow Coma Scale (GCS) scores of 9 to 15, as well as trauma control patients with GCS scores of 15 who did not have blunt head trauma. The primary outcome measure was the presence of intracranial lesions on initial CT scan. Blood samples were obtained in all patients within 6 hours of injury and measured by enzyme‐linked immunosorbent assay for GFAP (ng/mL). Results: A total of 257 children and youth were enrolled in the study and had serum samples drawn within 6 hours of injury for analysis: 197 had blunt head trauma and 60 were trauma controls. CT scan of the head was performed in 152 patients and traumatic intracranial lesions on CT scan were evident in 18 (11%), all of whom had GCS scores of 13 to 15. When serum levels of GFAP were compared in children and youth with traumatic intracranial lesions on CT scan to those without CT lesions, median GFAP levels were significantly higher in those with intracranial lesions (1.01, interquartile range [IQR] = 0.59 to 1.48) than those without lesions (0.18, IQR = 0.06 to 0.47). The area under the receiver operating characteristic curve (AUC) for GFAP in detecting children and youth with traumatic intracranial lesions on CT was 0.82 (95% confidence interval [CI] = 0.71 to 0.93). In those presenting with GCS scores of 15, the AUC for detecting lesions was 0.80 (95% CI = 0.68 to 0.92). Similarly, in children under 5 years old the AUC was 0.83 (95% CI = 0.56 to 1.00). Performance for detecting intracranial lesions at a GFAP cutoff level of 0.15 ng/mL yielded a sensitivity of 94%, a specificity of 47%, and a negative predictive value of 98%. Conclusions: In children and youth of all ages, GFAP measured within 6 hours of injury was associated with traumatic intracranial lesions on CT and with severity of TBI. Further study is required to validate these findings before clinical application.